Anti-MRSA activity of Stereospermum fimbriatum’s stem bark extracted using subcritical and supercritical carbon dioxide - Awang, Anis Fadhlina Izyani; Sheikh Mohamed, Hassan Ibrahim (IIUM Press, 2023)
Antibiotic resistance is a major challenge in healthcare, and this is further worsened by the presence of the dreadful Methicillin-resistant Staphylococcus aureus (MRSA) infection. This has urged scientists to find new effective antimicrobial drugs. Earth is enriched with natural resources such as plants that have been used traditionally to cure diseases. Stereospermum fimbriatum or “Chicha” had been used traditionally to treat several illnesses such as stomachache, earache, itchy skin, and postpartum illness. Thus, this study was designed to investigate the antibacterial potential of S. fimbriatum’s stem bark against MRSA. Subcritical (Sub-CO2) and supercritical carbon dioxide (Sup-CO2) extractions were used to extract the stem bark, with and without the addition of co-solvent (ethanol). The antimicrobial assay was carried out using disc diffusion (200, 400 and 600 µg/disc), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests. There was no anti-MRSA activity observed on both the SubCO2 and Sup-CO2 extracts without 10% ethanol. The most potent antiMRSA was observed by the Sup-CO2 extract with 10% ethanol with the MIC value of 500 µg/mL. Therefore, the use of ethanol (10 %) in the extraction increased the antibacterial activity of the S. fimbriatum’s extract against MRSA. These research findings could potentially facilitate future investigations into the utilization of green extraction methods to uncover promising antibacterial agents that can effectively target MRSA, a formidable pathogen. Future studies on the other parts of S. fimbriatum, its potential toxicity, and the possible mechanisms of action are needed to investigate its promising therapeutic values on MRSA infections.